Experience Realized in Edweek.org by a Black Student: an Appraisal Analysis of the Attitudinal Perspective - Rezza Fatwassani (Universitas PGRI Semarang, 2023)
The purpose of this research is to describe the message expressed by a black American student as contained in the Edweek portal which was published in 2020. Specifically, the research tried to identify the language choice of the published text. The research focused on the attitudinal perspective of the appraisal system. The identification includes the aspect of affect, judgment, and appreciation. As the data collection, a text about Almaw's experience